(untitled) (Proceedings of The International Conference on Economics and Development, 2017)
Corporate governance is one of the most important legislative domains of a business organization which has an impact on its profitability, growth and even sustainability of business. As business circumstances are vary the investors are differ with respect to incentives, risk-attitude, and different incentive strategies, the outcome of this process emerge as a kind of corporate governance practices. In order to protect investors from financial irregularities, misleading and fraudulent activities carried out by the firm the U.S Securities and Exchange Commission passed the act called Sarbanes-Oxley Act (SOX), whereas in India the Clause 49 of SEBI, is many times termed as Indian version of SOX but it has also been criticized for not being holistic in nature. Many of the corporate governance regulations are scattered in various clauses of Indian Companies act too. In this paper we aim to compare SOX and Indian regulations on corporate governance. We discuss the similarities, differences, areas of SOX superiority and suggest various improvements which if incorporated in Indian laws may lead to achievement of comprehensive regulation on corporate governance.